2014
DOI: 10.3892/br.2014.226
|View full text |Cite
|
Sign up to set email alerts
|

Aged black garlic extract inhibits HT29 colon cancer cell growth via the PI3K/Akt signaling pathway

Abstract: Abstract. Accumulating evidence indicates that aged black garlic extract (ABGE) may prove beneficial in preventing or inhibiting oncogenesis; however, the underlying mechanisms have not been fully elucidated. The present study aimed to investigate the effects of ABGE on the proliferation and apoptosis of HT29 colon cancer cells. Our results demonstrated that ABGE inhibited HT29 cell growth via the induction of apoptosis and cell cycle arrest. We further investigated the phosphatidylinositol 3-kinase̸protein ki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
66
0
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(74 citation statements)
references
References 20 publications
4
66
0
4
Order By: Relevance
“…The PI3K/Akt signaling pathway is involved in cell differentiation, proliferation, apoptosis and migration, and excessive activation of this pathway leads to cell dysfunction (26). A previous study indicated that PI3K/Akt signaling pathway activation occurs in association with DN, and high sugar or transforming growth factor-β1 levels can cause changes to certain podocyte proteins such as ZO-1 and CD2AP by activating this pathway (27).…”
Section: Discussionmentioning
confidence: 99%
“…The PI3K/Akt signaling pathway is involved in cell differentiation, proliferation, apoptosis and migration, and excessive activation of this pathway leads to cell dysfunction (26). A previous study indicated that PI3K/Akt signaling pathway activation occurs in association with DN, and high sugar or transforming growth factor-β1 levels can cause changes to certain podocyte proteins such as ZO-1 and CD2AP by activating this pathway (27).…”
Section: Discussionmentioning
confidence: 99%
“…As an inhibitor of PI3K can block the activation of Akt, the activation status of PI3K/Akt pathways can be predicted by observing the expression of p-Akt (10). Previous results have suggested that apoptosis plays an important role in cerebral neuron death after epilepsy (31). As a key component of survival signal, Akt is necessary to cellular survival triggered by growth factors, extra-cellular matrix and other stimulus (31).…”
Section: Discussionmentioning
confidence: 99%
“…Previous results have suggested that apoptosis plays an important role in cerebral neuron death after epilepsy (31). As a key component of survival signal, Akt is necessary to cellular survival triggered by growth factors, extra-cellular matrix and other stimulus (31). Activated Akt is a cellular survival factor that can help cells escape from programmed cell death by inactivating multiple effector molecules of apoptosis (32).…”
Section: Discussionmentioning
confidence: 99%
“…Azoxymethane (AOM), the oxide of azomethane, is procarcinogenic that induces colon cancer in rats and mice ( Escribano et al, 2004 andDong et al, 2014). AOM induces colon cancer via mechanisms that include glutathione depletion and impairing total antioxidant capacity so inducing oxidative stress in colonic cells of rats (Waly et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…AOM is a strong inducer of precancerous and dysplastic lesions (aberrant crypt foci, (ACF) in rodent colon and is particularly effective for the induction of colon adenocarcinoma (Dong et al, 2014). In addition, Venning et al, (2013) concluded that Azoxymethane (AOM) enhances early inflammation-induced colon crypt pathology in mice.…”
Section: Introductionmentioning
confidence: 99%